USULAN PERBAIKAN TATA LETAK FASILITAS PRODUKSI YARN PROCESSING DENGAN METODE SYSTEMATIC LAY OUT PLANNING (STUDI KASUS DI PT. AP Tbk.) - Tina Hernawati Suryatman; Hartono Hartono; Rifqi Maulana Fadil (Jurnal Teknik, 2019)
PT. AP Tbk. A company engaged in the integrated textile industry, one of the companies that produce various types of high-quality production in yarn manufacturing. Problems that occur at PT. AP Tbk. Superior in yarn processing facilities. In the layout production facility has not been used optimally, location settings are not optimal. found a step back that caused the distance to be far away. For that, it is necessary to restructure the layout of these machines so that the total distance of material handling is faster. Based on the results of research and data processing using a systematic Layout Lay out method, the layout is more efficient when compared to the layout before repair. With the SLP method, two alternative layout locations are produced which can minimize the distance of the material flow and the cost of material handling. Layout 1 can save a distance of 45 meters by issuing material handling costs of 3881.52 rupiah from the initial layout, while layout 2 can save a distance of 57 meters by looking for material handling costs of 4744.08 rupiah from the initial layout. Thus, layout 2 is more recommended so that activities and production results are more optimal and handling of cost material becomes smaller.